2013
DOI: 10.1007/s10310-012-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological functions of persistent Japanese cedar litter in structuring stream macroinvertebrate assemblages

Abstract: Stream macroinvertebrate assemblages are expected to be affected by the abundance and constitution of litter from surrounding forests. We compared forest floor cover, overland flow, stream environment, and stream macroinvertebrate assemblages between the catchments of a Japanese cedar plantation (CP) and a primary deciduous forest (DF). Both systems experience excessive deer browsing. Understory vegetation cover was higher in the DF than in the CP in summer, although cover was low (<20%), likely because of exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that the abundance or density of gammarid amphipods is significantly greater in streams that in drain Japanese cedar plantations than in those that drain deciduous broad-leaved forests (Hisabae, Sone & Inoue, 2010;Inoue et al, 2012;Sakai et al, 2013). These authors argue that greater invertebrate abundances/densities are the result of C. japonica litter Total calcium in water (μmol c L -1 ) Survival rate of Gammarus nipponensis P < 0.001 Fig.…”
Section: Geothelphusa Dehaanimentioning
confidence: 99%
“…Recent studies have shown that the abundance or density of gammarid amphipods is significantly greater in streams that in drain Japanese cedar plantations than in those that drain deciduous broad-leaved forests (Hisabae, Sone & Inoue, 2010;Inoue et al, 2012;Sakai et al, 2013). These authors argue that greater invertebrate abundances/densities are the result of C. japonica litter Total calcium in water (μmol c L -1 ) Survival rate of Gammarus nipponensis P < 0.001 Fig.…”
Section: Geothelphusa Dehaanimentioning
confidence: 99%
“…Recent studies have shown that the influence of topsoil on runoff generation on hillslopes can be very important. Such studies have mostly focused on overland flow (Miyata et al, 2007;Miyata et al, 2009;Gomi et al, 2010), while biomat flow has received less attention (Sidle et al, 2007;Sakai et al, 2013). Hillslope soils play an important role in redistributing precipitation into runoff, which contributes to streamflow, as well as soil water that affects infiltration and lateral subsurface and preferential flow (Sidle et al, 2000;Sidle et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This is attributable to longer periods of water submersion in the field, as Gomi et al (2018) showed that 240 days of submersion in streams decreased 137 Cs concentrations by 90% in Japanese cedar litter. In general, Japanese cedar litter is more persistent than broad-leaved deciduous litter is (Sakai et al, 2013); therefore, Cs leaching from litter may be prolonged, resulting in remarkably lower 137 Cs concentrations in aquatic litter.…”
Section: Discussionmentioning
confidence: 99%